2016
DOI: 10.1108/ijhg-01-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Difficult conversations? Engaging patients in reducing waste in health care

Abstract: Purpose – Reducing waste in health care can result in savings that could be used to meet the projected shortfall in NHS funding or to meet the care needs of vulnerable groups. Patients and their families can contribute to the identification and reduction of waste. To do so their understanding of the costs of health care and treatment needs to be increased. The paper aims to discuss these issues. Design/methodology/approach – The approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Several studies reported communication challenges arising from contributors' limited understanding of relevant project aspects due to lack of maturity, cultural, language, or literacy barriers (e.g., Steelman et al, 2019;Williams & James, 2008). Here, some authors described the inherent challenge of breaking down complex topics to make them relatable and understandable to lay audiences (Minogue et al, 2016;Williams & James, 2008). When discussing NHS funding with patients, Minogue et al (2016) found it difficult to identify appropriate methods of communication that would suit the needs of the various groups involved in the discussion.…”
Section: Challenges To Collaborationmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies reported communication challenges arising from contributors' limited understanding of relevant project aspects due to lack of maturity, cultural, language, or literacy barriers (e.g., Steelman et al, 2019;Williams & James, 2008). Here, some authors described the inherent challenge of breaking down complex topics to make them relatable and understandable to lay audiences (Minogue et al, 2016;Williams & James, 2008). When discussing NHS funding with patients, Minogue et al (2016) found it difficult to identify appropriate methods of communication that would suit the needs of the various groups involved in the discussion.…”
Section: Challenges To Collaborationmentioning
confidence: 99%
“…Here, some authors described the inherent challenge of breaking down complex topics to make them relatable and understandable to lay audiences (Minogue et al, 2016;Williams & James, 2008). When discussing NHS funding with patients, Minogue et al (2016) found it difficult to identify appropriate methods of communication that would suit the needs of the various groups involved in the discussion. Communication challenges also related to contributors' ability and/or desire to express themselves.…”
Section: Challenges To Collaborationmentioning
confidence: 99%
See 2 more Smart Citations
“…‘Difficult conversations? Engaging patients in reducing waste in the commissioning and delivery of health care’ [ 11 ], examined the potential role of patients in reducing waste recommended taking the learning from PPIE to engage in dialogue and partnership in the reduction of waste. This recommendation also has resonance for the reduction of waste in research.…”
Section: Introductionmentioning
confidence: 99%